2001
DOI: 10.1016/s0092-8674(01)00311-7
|View full text |Cite
|
Sign up to set email alerts
|

Apical Localization of wingless Transcripts Is Required for Wingless Signaling

Abstract: Many developing and adult tissues are comprised of polarized epithelia. Proteins that are asymmetrically distributed in these cells are thought to be localized by protein trafficking. Here we show that the distribution and function of the signaling protein Wingless is predetermined by the subcellular localization of its mRNA. High-resolution in situ hybridization reveals apical transcript localization in the majority of tissues examined. This localization is mediated by two independently acting elements in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
82
1
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(85 citation statements)
references
References 68 publications
1
82
1
1
Order By: Relevance
“…The transcript for the yeast plasma membrane protein Ist2 is actively transported along the acto-myosin network to the bud tip (Takizawa et al, 2000), and the protein is deposited locally (Juschke et al, 2004). wingless mRNA is localized apically in epithelial cells (Simmonds et al, 2001). In a stage 9 -10 Drosophila oocytes, gurken mRNA is transported and deposited exclusively in the dorsal/anterior corner (D/A; Neuman-Silberberg and Schupbach, 1993; Figure 1B).…”
Section: Introductionmentioning
confidence: 99%
“…The transcript for the yeast plasma membrane protein Ist2 is actively transported along the acto-myosin network to the bud tip (Takizawa et al, 2000), and the protein is deposited locally (Juschke et al, 2004). wingless mRNA is localized apically in epithelial cells (Simmonds et al, 2001). In a stage 9 -10 Drosophila oocytes, gurken mRNA is transported and deposited exclusively in the dorsal/anterior corner (D/A; Neuman-Silberberg and Schupbach, 1993; Figure 1B).…”
Section: Introductionmentioning
confidence: 99%
“…29 For example, proper function of the developmental signaling protein Wingless depends upon the apical location of its mRNA. 30 Since Df(3R) how heterozygotes do not dominantly suppress the phenotype of dp ov1 homozygotes, the suppression seen in how 3R-3 heterozygotes must be due to the effects of a mutant protein on Dumpy or its mRNA.…”
Section: Resultsmentioning
confidence: 99%
“…Recent genome-wide screen of RNAs localized in leading edge of migrating mammalian fibroblasts showed that in response to migratory stimuli, 50 different mRNAs (besides previously identified b-actin mRNA) accumulated, via microtubule mediated transport, in the fibroblast protrusions rich in actin cytoskeletal elements (Mili et al, 2008). In epithelial cells, the apical cytoskeleton containing cytokeratin, actin, and microtubules (Salas et al, 1997;Sugimoto et al, 2008) is enriched in localized wingless mRNA (Simmonds et al, 2001;Najand and Simmonds, 2007). In neurons, b-actin mRNA and actin filaments are localized in the growth cones and synapses (Zhang et al, 1999;Specht and Triller, 2008) and a subset of mRNAs localized at the synapse is thought to be responsible for the generation of synaptic plasticity (Kiebler and DesGroseillers, 2000;Czaplinski and Singer, 2006;Bramham and Wells, 2007).…”
Section: Structural Role Of Rna In the Cytoplasm Organization And Maimentioning
confidence: 99%